If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -9) + -1(1 + 7x) = -6x Reorder the terms: 2(-9 + x) + -1(1 + 7x) = -6x (-9 * 2 + x * 2) + -1(1 + 7x) = -6x (-18 + 2x) + -1(1 + 7x) = -6x -18 + 2x + (1 * -1 + 7x * -1) = -6x -18 + 2x + (-1 + -7x) = -6x Reorder the terms: -18 + -1 + 2x + -7x = -6x Combine like terms: -18 + -1 = -19 -19 + 2x + -7x = -6x Combine like terms: 2x + -7x = -5x -19 + -5x = -6x Solving -19 + -5x = -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -19 + -5x + 6x = -6x + 6x Combine like terms: -5x + 6x = 1x -19 + 1x = -6x + 6x Combine like terms: -6x + 6x = 0 -19 + 1x = 0 Add '19' to each side of the equation. -19 + 19 + 1x = 0 + 19 Combine like terms: -19 + 19 = 0 0 + 1x = 0 + 19 1x = 0 + 19 Combine like terms: 0 + 19 = 19 1x = 19 Divide each side by '1'. x = 19 Simplifying x = 19
| 5-0.7k=5 | | 9x^2-17x-2= | | 5m^2+13m+10= | | 10x^2-17x+3= | | -2(w+6)-6=4(w+3) | | 2a^2+9a+9= | | 7x+3x=9x-4 | | -5.1d+4.9-(2d+0.4)+2.8d= | | 6x^2+23x-18= | | 167+19c-16=1132 | | y=0.6(x-3)(x-9) | | 0.6(x-3)(x-9)= | | 24x^2+20x+4= | | 4x+14=-2x-22+12 | | 3x^2+28x-20=0 | | 3x^2+28-20=0 | | -6(w-1)=2(1-3w)-7 | | 7.05a-2=-4.25a+26.25 | | 12t=-68(fraction) | | 2a-3-a-2=10 | | 3r^3+18r^2=48r | | x+.75=.625 | | (x)=x^2-2x+5 | | (2a-3)-(a-2)=10 | | 9x-9=2x-16 | | 3(2-y)+4y=6 | | 5y+7y+6y-3= | | 2x-4x+5x-7x= | | x(x+3)=4x+12 | | -2(x)=-x^2-3x+3 | | 20a+12+11a=-47 | | [2x-7]=11 |